Literary gems from Sanskrit literature : a study of rare manuscripts - Wakankar, S. Y. (Delhi : Bharatiya Kala Prakashan, 2002)
Study with text of some works from Sanskrit litearature; based on rare manuscripts.
Includes bibliographical references.
English and Sanskrit.
Keywords: Sanskrit literature -- History and criticism; Sanskrit literature